Peran Stres Kerja Memediasi Pengaruh Konflik Pekerjaan-Keluarga Terhadap Kepuasan Kerja Karyawan pada LPD Desa Adat Kerobokan - Made Bagus Satrya Yudistira; Ida Bagus Ketut Surya; I Gede Riana; I Gde Ketut Warmika (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the influence of work-family conflict on job satisfaction, the influence of job stress on job satisfaction, and the role of job stress as a mediating variable in the relationship between work-family conflict and job satisfaction. This study used a quantitative approach with a sample of 58 respondents. Data collection was conducted using a questionnaire, while data analysis included validity tests, reliability tests, classical assumption tests, path analysis, and mediation tests. The results showed that work-family conflict had a negative and significant effect on job satisfaction and a positive and significant effect on job stress. Furthermore, job stress was shown to have a negative and significant effect on job satisfaction. The mediation test showed that job stress acted as a competitive partial mediator in the relationship between work-family conflict and job satisfaction. These findings emphasize the importance of managing work-family conflict and job stress to improve employee job satisfaction